تنمية الموارد البشرية في ظل تحديات الرقمنة في مؤسسات التعليم العالي - محمد, رافع (جامعة المسيلة, 2021)
Human resource development in light of the challenges of digitization in higher education institutions, a case study of Mohamed Boudiaf University in M'sila. Student preparation: kharbachi Elhacene, Rafaa Mohamed. Supervisor: D.Guerrouat younes Objectives of the study:Knowing the reality of human resource development in light of the challenges of digitization at Mohamed Boudiaf University in M'sila. Problem of study: The problem of the study lies in answering the main question: What is the reality of human resource development in light of the challenges of digitization at Mohamed Boudiaf University in M'sila? The Study population:The study population consisted of various administrative departments at Mohamed Boudiaf University, and the sample size was 103 individuals. Method and study tools:Use the descriptive approach to achieve the objectives of the study, answer its questions and test its hypotheses, and employ the questionnaire as a study tool. The most important results:Use the descriptive approach to achieve the objectives of the study, answer its questions and test its hypotheses, and employ the questionnaire as a study tool.
Keywords: Human resource development, digitization, Mohamed Boudiaf University in M'sila.